Developed security and privacy algorithms for cyber physical system - Dhuha Dheyaa Khudhur; Muayad Sadik Croock (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Cyber-physical system (CPS) is a modern technology in the cyber world, and it integrates with wireless sensor network (WSN). This system is widely used in many applications such as a smart city, greenhouse, healthcare, and power grid. Therefore, the data security and integrity are necessary to ensure the highest level of protection and performance for such systems. In this paper, two sides security system for cyber-physical level is proposed to obtain security, privacy, and integrity. The first side is applied the secure sockets layer (SSL)/transport layer security (TLS) encryption protocol with the internet of things (IoT) based message queuing telemetry transport (MQTT) protocol to secure the connection and encrypt the data exchange between the system's parties. The second side proposes an algorithm to detect and prevent a denial of service (DoS) attack (hypertext transfer protocol (HTTP) post request) on a Web server. The experiment results show the superior performance of the proposed method to secure the CPS by detecting and preventing the cyber-attacks, which infect the Web servers. They also prove the implementation of security, privacy and integrity aspects on the CPS.